A pillared-layered copper(i) halide-based metal–organic framework exhibiting dual emission, and piezochromic and thermochromic properties with a large temperature-dependent emission red-shift. Issue 4 (8th January 2018) - Xin, Bingjing; Sang, Jianwei; Gao, Yi; Li, Guanghua; Shi, Zhan; Feng, Shouhua
Abstract : A pillared-layered copper(i ) halide-based metal–organic framework [Cu6 I6 Br2 C16 H32 N4 ] exhibiting dual emission, and piezochromic and thermochromic properties with a large temperature-dependent emission red-shift is reported. Abstract : We report a new copper halide-based compound [Cu6 I6 Br2 C16 H32 N4 ] (1 ) with a 3D 2-fold interpenetrated framework structure. Upon excitation at 290 nm and 350 nm, compound1 shows dual emission at ca. 500 nm and ca. 530 nm. As the temperature decreased from 300 K down to 6 K, the luminescent properties of compound1 show large red shifts of 120 nm and 72 nm, respectively.